T-squared : theories and tactics in architecture and design - Krukowski, Samantha (Intellect Books, 2022)
This original collection explores the relationship between research that shapes art, architecture and design practices, and includes assignments that are developed by faculty for students. Samantha Krukowski is an artist, author and educator. Trained as an architect and art historian, she engages an interdisciplinary and intermodal practice that explores the nature of images and objects, the records of experience, the identity of place and the consequences of intervention. She works at the Kansas City Art Institute as The Sosland Family Chair of Foundation Studies; prior to joining KCAI, she was a faculty member at the University of Cincinnati (School of Design), Iowa State University (Department of Architecture), and the University of Texas at Austin (Department of Radio-Television-Film). Krukowski received a BA in Political Science at Barnard College/Columbia University (1988), an MA in Art History at Washington University in St. Louis (1992), an M. Arch. at The University of Texas at Austin (1997) and a Ph. D in Art History at The University of Texas at Austin (1999).